Antioxidant and Antimicrobial Activities of New Ethers, 1,3-Diazetidene-4-One and Thiazolidine-4-one Derivatives Containing Imidazobenzothiazole - alamery, zeena (Iraqi Journal of Science, 2024)
The synthesis of novel thiazolidinones 6-8A, diazetidenes 9-11A, and ethers 13-18A was described using 2-aminobenzathiazole and 4-bromophenacyl bromide as starting materials. The reaction of 2-aminobenzathiazole with 4-bromophenacyl bromide afforded the product A1 in 80% yield. Position 5 at the product A1 5-(4-bromophenyl)imidazo(2,1-b)benzothiazole used to form carbaldehyede group A2 under Vilsmeier-Huck conditions. Schiff bases 3-5A were then produced via condensation of A1 various aromatic amines. The products 3-5A were reacted with naphthyl isocyanate and thioacetic acid to give the compounds 6-8A (77-90% yields) and 9-11A (92-97% yields), respectively. The product 2A was reduced with NaBH4 to provide the corresponding alcohol 12A in an excellent yield (97%). This was followed by the reaction with aryl halides via the Williamson reaction to afford the desired ethers 13-18A in yields ranging from 50 to 96%. All of the prepared compounds were characterized by FT-IR spectroscopy, and some of them were characterized by 1H NMR and 13C NMR spectroscopy. A few products were evaluated for their antifungal, antibacterial, and antioxidant activities.